Counting Blessing Activity in Managing Psychological Well-Being for University Students - Akhnaf, Ardhito Faza; Nurmayanti, Alsya Alifia; Kusuma, Elda; Syahda, Marsha Aurellia; Febriandini, Thalida; Chasyavera, Feby Athasya; Qudsyi, Hazhira (Psikis : Jurnal Psikologi Islami, 2024)
University students are individuals who must always adapt amidst the rapid and uncertain changing times. Good psychological well-being is needed to achieve optimization in every activity, both academic and non-academic. This study aimed to determine the effectiveness of counting blessings in managing the univesity students’ psychological well-being. This study applied a nonrandomized control group design with a pretest and posttest, consisting of 28 participants having psychological well-being from low to moderate levels. The participants were divided into two groups, the experimental group and the control group. The levels of psychological well-being were measured by using The Scale of Psychological Well-being (SPWB) developed by Ryff (2014) adapted by Rihlati (2018). Psychological well-being scores of the pretest and posttest were processed by SPSS 25 for Windows. This study indicated a p value of 0.394 (p>0.05), meaning that there were no significant different levels of psychological well-being between the group performing counting blessings and the group not performing counting blessings. Then, this study also found that there were significantly different levels of psychological well-being of the participants before and after performing counting blessings with a p-value of 0.002 (p>0.05). The efforts made by each student to interpret every positive thing in their daily life are beneficial to help them have good psychological well-being.